Role of Multiple Serial Casting beyond Standard Casting Technique in Managing Club Feet - Muhammad Zaib Tunio, Muhammad Arshad Aleem, Tanweer Hussain, Zain-ul-Abideen, Muhammad Saleem Akhtar, Naveed Gul (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To find the role of multiple serial casting beyond standard casting technique in managing club feet. Methodology: Cohort prospective study. Department of Orthopaedic, Chandka Medical College Hospital Larkana from July 1, 2021 to June 30, 2022. One hundred cases were enrolled. The Pirani scoring system was applied for detailed monitoring of the severity and treatment of clubfoot, and the Ponseti method technique was performed. Foot or feet were cast and fastened in an abduction brace at 95% of the correction rate being achieved. All children below two years of age who had one or both feet clubbed were included in this study. Results: The majority of the children visiting the hospital setting for treatment of clubfoot were within the age group of 0–5 months, followed by 6–12 months in 55% and 31% of the children, respectively. About 70% of the children with club feet were boys, with only 30% being girls. The baseline Pirani score was 3.47±0.523, while it decreased significantly to 0.0321±0.135 as the final Pirani score. The outcomes of the study showed that 68% of the children had excellent treatment, 10% had really good treatment, and 18% had fair treatment. Conclusion: Serial casting is a favourable technique for the treatment of clubfoot, wherein it assists in the maintenance of foot balance and proper development. Keywords: Multiple serial casting, Standard casting, Club feet